Personality as a Core Organizing Factor in Mind–Body Health: A Computational Modeling Study - Carvalho , José; Santos Figueiredo , Clarice; Raposo , Antonio (Journal of Personality and Psychosomatic Research (JPPR), 2026)
This study aimed to examine whether personality traits function as a core organizing system underlying mind–body health by integrating multivariate and computational modeling approaches. A cross-sectional design was employed with an adult sample recruited from Portugal. Participants completed validated self-report instruments assessing personality traits and multiple domains of mind–body health, including physical and mental health, perceived stress, affective balance, and sleep quality. Data were first examined using descriptive statistics and correlational analyses to establish basic relationships among variables. Structural equation modeling was then applied to test a theoretically informed model in which personality traits predicted latent dimensions of mind–body health. To complement explanatory analyses, machine learning techniques, including linear and non-linear predictive models, were used to estimate the extent to which personality traits could predict composite mind–body health outcomes. Model performance was evaluated using explained variance and error indices, and feature importance analyses were conducted to identify the relative contribution of each personality trait. Inferential analyses revealed significant and systematic associations between personality traits and all major mind–body health indicators. Neuroticism emerged as a strong positive predictor of stress, negative affect, and sleep disturbances and a strong negative predictor of physical and mental health, whereas Conscientiousness showed the opposite pattern, functioning as a robust protective factor. Structural equation modeling demonstrated that personality traits exerted simultaneous and differential effects on latent health, stress–affect, and sleep regulation factors, with excellent model fit indices. Machine learning models significantly outperformed traditional linear regression, indicating non-linear and interactive relationships between personality and health, with Neuroticism and Conscientiousness showing the highest predictive importance. The findings support the conceptualization of personality as a central organizing factor in mind–body health, shaping the structure, regulation, and predictability of physical and psychological well-being, and highlight the value of computational approaches for advancing integrative psychosomatic models.